A Putative P-Type ATPase Regulates the Secretion of Hydrolytic Enzymes, Phospholipid Transport, Morphogenesis, and Pathogenesis in Phytophthora capsici - Yang, Chengdong; Zheng, Bowen; Wang, Rongbo; Chang, Hongyang; Liu, Peiqing; Li, Benjin; Norvienyeku, Justice; Chen, Qinghe (Frontiers in Plant Science, 2022)
Phytophthora capsici is an important plant pathogenic oomycete with multiple hosts. The P4-ATPases, aminophospholipid translocases (APTs), play essential roles in the growth and pathogenesis of fungal pathogens. However, the function of P4-ATPase in P. capsici remains unclear. This study identified and characterized PcApt1, a P4-ATPase Drs2 homolog, in P. capsici. Deletion of PcAPT1 by CRISPR/Cas9 knock-out strategy impaired hyphal growth, extracellular laccase activity. Cytological analyses have shown that PcApt1 participates in phosphatidylserine (PS) transport across the plasma membrane. Also, we showed that targeted deletion of PcAPT1 triggered a significant reduction in the virulence of P. capsici. Secretome analyses have demonstrated that secretion of hydrolytic enzymes decreased considerably in the PcAPT1 gene deletion strains compared to the wild-type. Overall, our results showed that PcApt1 plays a pivotal role in promoting morphological development, phospholipid transport, secretion of hydrolytic enzymes, and the pathogenicity of the polycyclic phytopathogenic oomycete P. capsici. This study underscores the need for comprehensive evaluation of subsequent members of the P-type ATPase family to provide enhanced insights into the dynamic contributions to the pathogenesis of P. capsici and their possible deployment in the formulation of effective control strategies.